Simulation and result analysis of digital signal processing related algorithms using MATLAB - Koh, Chee Meng. (2011)
This project aims to study on the existing methods for logarithmic approximations in terms of accuracy so that the nature of errors of the approximations is better understood, which in terms will facilitate the search for new methods or ways to improve on the accuracy of logarithmic approximations. This report gives an overview of the seven chosen logarithmic approximations, specifically Mitchell’s approximation, M. Combet, H. Van Zonneveld and L. Verbeek’s approximation, Samuel L. SanGregory, Charles Brothers and David Gallagher’s approximation, Khalid H. Abed and Raymond E. Siferd’s approximation, Zhijun Li, Jianping An, Miao Tang and Jing Yang’s approximation and Tso-Bing Juang, Sheng-Hung Chen and Huang-Jia Cheng’s approximation. In addition, this report also covers the methodology of how these logarithmic approximations are modeled using MATLAB. The process of data acquisition and the plotting of graph for the maximum and minimum errors and percentage errors of the logarithmic approximations are also detailed in this report. Furthermore, the problems encountered and the solutions used during the process of acquiring data and plotting the error graphs will also be shown in this report. Lastly, the comparison and analytical results for the errors and percentage errors of the logarithmic approximations are presented.